Influenza viruses with B/Yamagata- and B/Victoria-like neuraminidases are differentially affected by mutations that alter antiviral susceptibility. (18th March 2015) - Farrukee, Rubaiyea; Leang, Sook-Kwan; Butler, Jeff; Lee, Raphael T. C.; Maurer-Stroh, Sebastian; Tilmanis, Danielle; Sullivan, Sheena; Mosse, Jennifer; Barr, Ian G.; Hurt, Aeron C.
Abstract: Objectives: The burden of disease due to influenza B is often underestimated. Clinical studies have shown that oseltamivir, a widely used neuraminidase inhibitor (NAI) antiviral drug, may have reduced effectiveness against influenza B viruses. Therefore, it is important to study the effect of neuraminidase mutations in influenza B viruses that may further reduce NAI susceptibility, and to determine whether these mutations have the same effect in the two lineages of influenza B viruses that are currently circulating (B/Yamagata-like and B/Victoria-like). Methods: We characterized the effect of 16 amino acid substitutions across five framework residues and four monomeric interface residues on the susceptibility to four different NAIs (oseltamivir, zanamivir, peramivir and laninamivir). Results: Framework residue mutations E117A and E117G conferred highly reduced inhibition to three of the four NAIs, but substantially reduced neuraminidase activity, whereas other framework mutations retained a greater level of NA activity. Mutations E105K, P139S and G140R of the monomeric interface were also found to cause highly reduced inhibition, but, interestingly, their effect was substantially greater in a B/Victoria-like neuraminidase than in a B/Yamagata-like neuraminidase, with some susceptibility values being up to 1000-fold different between lineages. Conclusions: The frequency and the effect of key neuraminidase mutations on neuraminidase activity and NAI susceptibility can differ substantially between the two influenza B lineages. Therefore, future surveillance, analysis and interpretation of influenza B virus NAI susceptibility should consider the B lineage of the neuraminidase in the same manner as already occurs for different influenza A neuraminidase subtypes.